Analysis of Family Support and Patient Motivation in Diabetes Mellitus Diet Compliance - Nurwijayanti Nurwijayanti; Panca Radono (Indonesian Journal of Global Health Research, 2026)
Dietary adherence is a key pillar in the management of diabetes mellitus (DM) to prevent chronic complications. The phenomenon at RSU ‘Aisyiyah Ponorogo shows that even though patients have sufficient knowledge, many still have difficulty maintaining their diet. External factors, such as family support, and internal factors, such as patient motivation, are strongly suspected as determinants of the success of long-term dietary management. The purpose of this study is to examine how patient motivation and family support relate to dietary adherence in patients with diabetes mellitus at the Internal Polyclinic of RSU "Aisyiyah Ponorogo". This study used a cross-sectional methodology and a quantitative correlational study design. Every DM patient that visits the Internal Polyclinic is included in the study population. Consecutive sampling was the method utilized for sampling. A family support questionnaire, a motivation questionnaire, and a dietary adherence questionnaire (such as a modified MMAS-8) were utilized as research instruments. Logistic regression or the Spearman rank statistical test were used to analyze the data. The research instrument was tested for validity using Product Moment correlation and declared valid because all calculated r values were > r table (0.263). The reliability test using Cronbach's Alpha showed an α value > 0.60, so the instrument was declared reliable and suitable for use. It is anticipated that the study's findings would demonstrate a strong correlation between self-motivation and dietary adherence as well as between family support and dietary adherence. Compliance with the DM diet program is mostly driven by a patient's high level of intrinsic motivation and a supportive family in supplying a diet menu.The degree of dietary compliance is significantly influenced by patient motivation and family support.